9.4.33 problem problem 44

Internal problem ID [997]
Book : Differential equations and linear algebra, 4th ed., Edwards and Penney
Section : Section 7.3, The eigenvalue method for linear systems. Page 395
Problem number : problem 44
Date solved : Monday, January 27, 2025 at 03:22:48 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=147 x_{1} \left (t \right )+23 x_{2} \left (t \right )-202 x_{3} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=-90 x_{1} \left (t \right )-9 x_{2} \left (t \right )+129 x_{3} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=90 x_{1} \left (t \right )+15 x_{2} \left (t \right )-123 x_{3} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.032 (sec). Leaf size: 73

dsolve([diff(x__1(t),t)=147*x__1(t)+23*x__2(t)-202*x__3(t),diff(x__2(t),t)=-90*x__1(t)-9*x__2(t)+129*x__3(t),diff(x__3(t),t)=90*x__1(t)+15*x__2(t)-123*x__3(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= c_1 \,{\mathrm e}^{6 t}+c_2 \,{\mathrm e}^{-3 t}+c_3 \,{\mathrm e}^{12 t} \\ x_{2} \left (t \right ) &= \frac {c_1 \,{\mathrm e}^{6 t}}{7}-\frac {2 c_2 \,{\mathrm e}^{-3 t}}{3}-\frac {3 c_3 \,{\mathrm e}^{12 t}}{5} \\ x_{3} \left (t \right ) &= \frac {5 c_1 \,{\mathrm e}^{6 t}}{7}+\frac {2 c_2 \,{\mathrm e}^{-3 t}}{3}+\frac {3 c_3 \,{\mathrm e}^{12 t}}{5} \\ \end{align*}

Solution by Mathematica

Time used: 0.005 (sec). Leaf size: 188

DSolve[{D[ x1[t],t]==147*x1[t]+23*x2[t]-202*x3[t],D[ x2[t],t]==-90*x1[t]-9*x2[t]+129*x3[t],D[ x3[t],t]==90*x1[t]+15*x2[t]-123*x3[t]},{x1[t],x2[t],x3[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to \frac {1}{6} e^{-3 t} \left (6 c_1 \left (10 e^{15 t}-9\right )+c_2 \left (7 e^{9 t}+5 e^{15 t}-12\right )-c_3 \left (-7 e^{9 t}+85 e^{15 t}-78\right )\right ) \\ \text {x2}(t)\to \frac {1}{6} e^{-3 t} \left (-36 c_1 \left (e^{15 t}-1\right )+c_2 \left (e^{9 t}-3 e^{15 t}+8\right )+c_3 \left (e^{9 t}+51 e^{15 t}-52\right )\right ) \\ \text {x3}(t)\to \frac {1}{6} e^{-3 t} \left (36 c_1 \left (e^{15 t}-1\right )+c_2 \left (5 e^{9 t}+3 e^{15 t}-8\right )-c_3 \left (-5 e^{9 t}+51 e^{15 t}-52\right )\right ) \\ \end{align*}